The association between oral candidiasis and severity of chemoradiotherapy-induced dysphagia in head and neck cancer patients: A retrospective cohort study. (January 2020) - Saito, Hirotake; Shodo, Ryusuke; Yamazaki, Keisuke; Katsura, Kouji; Ueki, Yushi; Nakano, Toshimichi; Oshikane, Tomoya; Yamana, Nobuko; Tanabe, Satoshi; Utsunomiya, Satoru; Ohta, Atsushi; Abe, Eisuke; et al.
Highlights: Oral candidiasis (OC) aggravated dysphagia in chemoradiation for HNC. OC patients required higher doses of opioids. Early diagnosis of chemoradiation-associated OC seems difficult. Antifungal prophylaxis may reduce the severity of mucositis and dysphagia. Abstract: Background and purpose: Concurrent chemoradiotherapy (CCRT) for head and neck cancer (HNC) is a risk factor for oral candidiasis (OC). As Candida spp. are highly virulent, we conducted a retrospective study to determine whether OC increases the severity of dysphagia related to mucositis in HNC patients. Patients and methods: We retrospectively analyzed the cases of consecutive patients with carcinomas of the oral cavity, pharynx, and larynx who underwent CCRT containing cisplatin (CDDP) at our hospital. The diagnosis of OC was based on gross mucosal appearance. We performed a multivariate analysis to determine whether OC was associated with the development of grade 3 dysphagia in the Radiation Therapy Oncology Group (RTOG) Acute Toxicity Criteria. The maximum of the daily opioid doses was compared between the patients with and without OC. Results: We identified 138 HNC patients. OC was observed in 51 patients (37%). By the time of their OC diagnosis, 19 (37%) had already developed grade 3 dysphagia. Among the 30 patients receiving antifungal therapy, 12 (40%) showed clinical deterioration. In the multivariate analysis, OC was independently associated with grade 3 dysphagia (OR 2.75; 95%CI 1.22–6.23; p = 0.015). The patients with OC required significantly higher morphine-equivalent doses of opioids (45 vs. 30 mg/day; p = 0.029). Conclusion: Candida infection causes refractory dysphagia. It is worth investigating whether antifungal prophylaxis reduces severe dysphagia related to candidiasis.